Comparative Outcomes Of Laparoscopy-Assisted Vs. Open Distal Gastrectomy For Gastric Cancer In The Elderly: A Systematic Review - Yanita, Bella; Wintoko, Rizal; Farishal, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract Background: Gastric cancer, prevalent among the elderly, presents considerable health challenges due to the age-related decline in immune function. Surgical management options include laparoscopic-assisted gastrectomy (LDG) and open gastrectomy (ODG). Methods: This systematic review followed PRISMA guidelines, using PubMed, Scopus, and Cochrane Library to identify cohort and case-control studies published between 2014–2024. Studies comparing LDG and ODG in patients aged 70 and older, reporting on outcomes such as recovery time, postoperative complications, and survival rates, were included. Data extraction and bias assessment were conducted, and a qualitative synthesis of results was performed. Results: LDG was associated with longer operating times compared to ODG in three out of five studies (p < 0.01). However, LDG consistently resulted in significantly lower intraoperative blood loss (p < 0.01) and faster recovery, evidenced by shorter time to first flatus and oral intake (p < 0.01) and reduced hospital stays across all studies (p < 0.05). LDG was associated with fewer postoperative complications in two studies (p < 0.05), although other studies showed no significant difference in complication rates. Discussion: Five retrospective cohort studies with a total of 317 LDG and 256 ODG were included in the qualitative analysis. LDG was associated with significantly reduced intraoperative blood loss, faster recovery times, and shorter hospital stays, making it a favorable option for elderly patients. While LDG generally involved longer operating times, it did not lead to increased postoperative complications. Conclusion: LDG offers several short-term advantages compared to ODG, suggesting it may be a safer and more effective approach for elderly gastric cancer patients. However, further studies are needed to assess long-term outcomes and confirm the overall efficacy of LDG in this population. Keywords: Gastric Cancer, Eldery Patients, Comparative, Systematic Review, Survival Rates